High-temperature rheological behavior and fatigue performance of lignin modified asphalt binder. (10th January 2020) - Gao, Junfeng; Wang, Hainian; Liu, Chaochao; Ge, Dongdong; You, Zhanping; Yu, Miao
Highlights: Lignin increased activation energy, elastic component, rutting resistance of asphalt. Incorporation of lignin could retard oxidation reactions occurred in the asphalt. Lignin modified asphalt had high percent recovery and low stress sensitivity. The incorporation of lignin degraded the fatigue life of the asphalt. Abstract: The objective of this study was to introduce lignin as a bio-additive to modify the base asphalt and investigate the high-temperature rheological performances of lignin modified asphalts and virgin asphalt. In this study, asphalt PG 58-28 was selected as the virgin asphalt, and four contents, 2%, 4%, 6% and 8%, of the total binder by weight of lignin were incorporated in the base binder. Rotational viscosity (RV), dynamic shear rheometer (DSR), and multiple stress creep recovery (MSCR) tests were conducted to characterize the rheological performances of different types of asphalts. Linear amplitude sweep (LAS) test was employed to evaluate the fatigue performance. The results showed that the incorporation of lignin increased the viscosity of virgin asphalt at different rotational speeds. The activation energy showed an increasing trend as the lignin increased compared with the virgin asphalt. Meanwhile, the lignin incorporated into the asphalt binder increased the elastic components, and improved the resistance of asphalt binder to the permanent deformation regardless of the lignin contents. The addition of lignin in the asphalt binder could retard oxidation reactions that occurred in the asphalt during the rolling thin film oven aging. In addition, the incorporation of lignin may degrade the fatigue life of asphalt. However, when the content of lignin was less than 8%, the reduction was small. This study could provide a prospective foundation for the utilization of lignin extracted from waste biomass as an exceptional and renewable bio-additive in the field of asphalt pavement engineering.